Strategi Manajemen Dan Faktor-Faktor Yang Mempengaruhi Tingkat Ketahanan Umkm Di Masa Pandemi Covid-19 (Studi Kasus: Kecamatan Bangun Purba, Deli Serdang) - Syafri Fadillah Marpaung; Riski Halomoan; Risdan Azhari Lubis (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
Abstract This study aims to confirm the 5P theory of Henri Mirtberg through the list of questions that have been provided. This study also explores the answers to questions posed by Pedersen and Ritter (2020) 5 (five) Ps, namely: position, plan, perspective, project, and prepare which were adapted from Henry Mintzberg's 5P theory as well as E-Commerce and financial literacy. This type of research uses quantitative methods which consist of samples and numerical data. The type of data used is primary data. The primary data in this study came from responses to questionnaires. The population of this research is the MSME actors in Bangun Purba sub-district as many as 369 and the determination of the sample uses the slovin formula so that the number of samples is 192 respondents. The technique of collecting data is by using a questionnaire and then processing it with validity and reliability tests. The data analysis technique used statistical tests. Plan has a significant effect on the resilience of MSMEs in the Bangun ancient sub-district. Ploy has a significant effect on the resilience of MSMEs in the Bangun ancient sub-district. Pattern has a significant effect on the resilience of MSMEs in the Bangun ancient sub-district. Position has a significant effect on the resilience of MSMEs in the Bangun ancient subdistrict. Perspective has a significant effect on the resilience of MSMEs in the Bangun ancient sub-district. E-Commerce has a significant effect on the resilience of MSMEs in the Bangun ancient sub-district. Financial literacy has a significant effect on the resilience of MSMEs in the Bangun ancient sub-district.